The ancient Mediterranean environment between science and history - Harris, William V. (William Vernon) (Columbia studies in the classical tradition ;, 2013)
The product of a collaboration between scientists, historians and archaeologists, this book breaks new ground in the study of the long-term interaction between environmental factors, including climate, and human beings.